Factors Affecting Knowledge and Adoption of Integrated Nutrient Management (INM) Practices in Rice Wheat Cropping System (RWCS) in Haryana, India - Mohit; Satpal Singh; Anil Sidaray Chikkalaki; Jagadeesh, M. S.; Veershetty (Archives of Current Research International, 2024)
The study was conducted in 2022 in Haryana. Following the ex-post facto methodology, this study assessed the profile characteristics of farmers practicing the Rice-Wheat Cropping System (RWCS) and their knowledge and adoption of Integrated Nutrient Management (INM) practices. The majority of respondents were middle-aged, with a significant portion possessing education up to the higher secondary level. Most respondents belonged to the general category and practiced farming as their primary occupation. The analysis revealed that larger landholdings positively influenced socio-economic status, leading to better adoption of INM practices. While the knowledge and adoption of INM practices varied among respondents, education, landholding, farming experience, social participation, and extension contacts were significantly correlated with higher awareness and adoption levels. The findings suggest the need for targeted educational and awareness programs to enhance the adoption of INM practices among farmers, particularly focusing on younger and more educated individuals.